2008
DOI: 10.1590/s0102-311x2008000700013
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de dois critérios utilizados no Programa Saúde da Família na priorização do tratamento da cárie entre crianças de 5 a 12 anos

Abstract: O objetivo deste trabalho foi avaliar dois critérios utilizados no Programa Saúde da Família para determinação da prioridade do atendimento odontológico curativo da cárie. O estudo foi feito no Município de Ipiguá, São Paulo, Brasil, entre 538 crianças de 5 a 12 anos de idade. Realizou-se o exame bucal e preenchimento de dois critérios de classificação para as mesmas crianças a fim de avaliar as prioridades no atendimento odontológico curativo resultantes de cada um dos critérios. Com base na atividade da doen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Despite these difficulties, there are initiatives of professional oral health practices based on health education 17,18 and health promotion [19][20][21] . These produce improvements in health conditions and practices (20)(21)(22) as they are effective in reducing the weaknesses of specific groups and health inequity 22 , despite reduced intersectoriality [21][22][23][24][25][26][27][28] . Another important theme evaluated was the insertion of OHT into the FHS, certainly a contentious process for most professionals as it involves the dynamic of the encounter between two not well resolved dimensions of a dentist's identity: academic training often focused on individual action and work in a multidisciplinary team of which he/she must be a part 14,22,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these difficulties, there are initiatives of professional oral health practices based on health education 17,18 and health promotion [19][20][21] . These produce improvements in health conditions and practices (20)(21)(22) as they are effective in reducing the weaknesses of specific groups and health inequity 22 , despite reduced intersectoriality [21][22][23][24][25][26][27][28] . Another important theme evaluated was the insertion of OHT into the FHS, certainly a contentious process for most professionals as it involves the dynamic of the encounter between two not well resolved dimensions of a dentist's identity: academic training often focused on individual action and work in a multidisciplinary team of which he/she must be a part 14,22,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al 20 states that the classification of caries risk proposed by the Department of Health of the State of São Paulo (SES/SP), which was used in this study, is based on scientific evidence and also on several municipal experiences carried out in the state, and which is certainly not the only way to classify individuals, but it is a tool that is widely used because of its the ease and practicality 20 . Another classification of caries risk, proposed by the Department of Health of the Federal District, has shown to be very different in determining the priority of dental care focused on caries when compared with that of the state of São Paulo, however it indicates that it should be prioritized together with a family risk classification 10 , as adopted in our study. It was not sought to analyze the limitations that such classifications may present, as several studies have shown, that the diagnostic threshold from cavity lesion does not inform epidemiologists and health managers about which lesions/individuals need preventive and non-invasive treatment.…”
Section: Discussionmentioning
confidence: 66%
“…It is well known that the adult population is at greater risk of developing periodontal disease, while children are at greater risk of developing tooth decay, and, in order to establish individual risk for planning purposes, it can be considered the most significant event for the population group to be examined and classified 6 . For such purpose, the Department of Health of the State of São Paulo proposes the individual risk classification, considering the disease activity to determine the priority in health care, for tooth decay and periodontal disease 10 , using two tools that classify individuals in three categories for the mentioned morbidities, which are: Low risk -no signs of disease activity and no previous history of disease; Moderate risk -no signs of disease activity, but with a previous history of disease; and High risk -with presence of disease activity, with or without previous history of disease 7 . Studies relating the household socioeconomic context and oral morbidities (tooth decay and periodontal disease) show that families at risk are twice as likely to present dental caries disease 11 and that gingivitis and periodontitis present higher prevalence in populations with worse socioeconomic indicators such as income and education level 12 .…”
Section: Introductionmentioning
confidence: 99%
“…These results may be indicative of the influence of unfavorable social and environmental factors in areas where the study population lives and whose accumulation of sociobiological risks for the occurrence and progression of caries may be continuously increasing with age [20][21][22][23][24]. In addition to revealing difficulties related to oral health surveillance actions planned for the study areas aimed at preventing and controlling early caries and monitoring groups at greater risk of having pain episodes of dental origin that require priority access to clinical treatment [25], as this condition has a negative impact on the quality of life of children and their families [21].…”
Section: Discussionmentioning
confidence: 99%